A Review of Sugar-Based Confectionery: Properties and Types of Products (International Journal of Food and Nutritional Sciences, 2022)
A sweet goods or confectionery is a group of products, rich in carbohydrates with characteristic physical and chemical properties. Due to continuous improvement and innovation in product confectionery products are accepted by all age groups across the globe. Confectionery product shows different physical state like liquid, glassy, amorphous, crystalline, and partial crystalline. During formulation and manufacturing confectionery products need to consider different properties of confectionery ingredients and the behaviour of the final product. Solubility, Glass Transition Temperature, Boiling Point Elevation and Moisture Content are the most important properties of sweet goods. Confectionery products are categorised based on product types. The Most Commonly product consider confectionery products are Hard-Boiled Candy, Cotton Candy, Fondant and Cream, Marshmallows, Nougat, Caramel and Fudge, Gum, Jelly and Gummy Candies, Compressed Tablets and Wafers, Sugar Panned Candies. This review article tries to summarize the introduction of confectionery, the basic properties of confectionery, different types of confectionery products and different quality parameters of confectionery products.